Efficacy, immunogenicity and safety of the HPV‐16/18 AS04‐adjuvanted vaccine in healthy Chinese women aged 18–25 years: Results from a randomized controlled trial. Issue 11 (20th May 2014) - Zhu, Feng‐Cai; Chen, Wen; Hu, Yue‐Mei; Hong, Ying; Li, Juan; Zhang, Xun; Zhang, Yi‐Ju; Pan, Qin‐Jing; Zhao, Fang‐Hui; Yu, Jia‐Xi; Zhang, Yan‐Shu; Yang, Xiaoping; et al.
Abstract : This phase II/III, double‐blind, randomized trial assessed the efficacy, immunogenicity and safety of the human papillomavirus (HPV)‐16/18 AS04‐adjuvanted vaccine in young Chinese women (ClinicalTrials.gov registration NCT00779766). Women aged 18–25 years from Jiangsu province were randomized (1:1) to receive HPV vaccine ( n = 3, 026) or Al(OH)3 control ( n = 3, 025) at months 0, 1 and 6. The primary objective was vaccine efficacy (VE) against HPV‐16/18 associated 6‐month persistent infection (PI) and/or cervical intraepithelial neoplasia (CIN) 1+. Secondary objectives were VE against virological and clinical endpoints associated with HPV‐16/18 and with high‐risk HPV types, immunogenicity and safety. Mean follow‐up for the according‐to‐protocol cohort for efficacy (ATP‐E) was ∼15 months after the third dose. In the ATP‐E (vaccine = 2, 889; control = 2, 894), for initially HPV DNA negative and seronegative subjects, HPV‐16/18 related VE (95% CI) was 94.2% (62.7, 99.9) against 6‐month PI and/or CIN1+ and 93.8% (60.2, 99.9) against cytological abnormalities. VE against HPV‐16/18 associated CIN1+ and CIN2+ was 100% (−50.4, 100) and 100% (−140.2, 100), respectively (no cases in the vaccine group and 4 CIN1+ and 3 CIN2+ cases in the control group). At Month 7, at least 99.7% of initially seronegative vaccine recipients had seroconverted for HPV‐16/18; geometric mean antibody titres (95% CI) were 6, 996 (6, 212 to 7, 880) EU/mL for anti‐HPV‐16 and 3, 309 (2, 942 to 3, 723) EU/mL for anti‐HPV‐18. Safety outcomes between groups were generally similar. The HPV‐16/18 AS04‐adjuvanted vaccine is effective, immunogenic and has a clinically acceptable safety profile in young Chinese women. Prophylactic HPV vaccination has the potential to substantially reduce the burden of cervical cancer in China. Abstract : What's New? With an estimated 75, 000 new cases and 34, 000 women dying from the disease annually, cervical cancer is a major public‐health concern in China. This is the first large scale randomised clinical trial of a human papillomavirus (HPV) vaccine in China. The vaccine was found to be effective, immunogenic, and to have a clinically acceptable safety profile in young Chinese women. Prophylactic HPV vaccination thus has the potential to substantially reduce the burden of cervical cancers and precancers in China.